Política pública de assistência social em análise : história, valores e práticas - Souza, Carolina Rodrigues Alves de (2012)
This paper intends to put under analysis, through the psychoanalytical method, the work of a psychologist who becomes here a researcher on social service s politics, whose job is to execute social-educational measures without liberty restraints. We initiate from this experience and from a set of questions asked about it and, especially, about being a psychologist and/or a social worker on that space. On this purpose, we look over shared and historically conditioned ideals that, due to their attributes, operate their practices and impose their values on that field. For that, we use the theoretical and methodological contribution of psychoanalysis, and therefore we confirm it as a tool of listening institutional spaces, politics and history. According with the field that set us place and with the elements it gives us, we make a few analysis about the positions occupied by the family and by the childhood and about the modern value associated to them, the one of education, where permeate also the senses of poverty, work and responsibility. Ahead on the same purpose, we discuss about imputability and guilt and then we finally get to the question: is there any possibility of transgression, in other words, of breaking a given normative system? What we want, therefore, is to dispose to our reader the elements found on our experience in order to constitute them into instruments of transformation and reconfiguration of both our practice and others which find in them resemblance and identification.